2016
DOI: 10.1042/bst20160016
|View full text |Cite
|
Sign up to set email alerts
|

The conservation of phosphate-binding residues among PHT1 transporters suggests that distinct transport affinities are unlikely to result from differences in the phosphate-binding site

Abstract: The plant PHosphate Transporter 1 (PHT1) family of membrane proteins belongs to the major facilitator super family and plays a major role in the acquisition of inorganic phosphate (Pi) from the soil and its transport within the plant. These transporters have been well characterized for expression patterns, localization, and in some cases affinity. Furthermore, the crystal structure of a high-affinity eukaryotic phosphate transporter from the fungus Piriformospora indica (PiPT) has revealed important informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Their functions were characterized by heterologous expression in Saccharomyces cerevisiae Pi transporter deficient mutants and Xenopus oocytes. PHT1 transporters are found to have 12 transmembrane segments and belong to the Major Facilitator Superfamily (MFS) of transporters 5 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Their functions were characterized by heterologous expression in Saccharomyces cerevisiae Pi transporter deficient mutants and Xenopus oocytes. PHT1 transporters are found to have 12 transmembrane segments and belong to the Major Facilitator Superfamily (MFS) of transporters 5 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of 32 P orthophosphate uptake at 22°C at a range of phosphate concentrations showed a biphasic plot consistent with low‐ and high‐affinity transport components (Figure 4b) as described previously (Ullrich‐Eberius et al., 1984). The Spirodela genome has three putative phosphate transporters of the PHT1 family which could encode the transporters responsible for this activity (Table S1, Figure S1) but it is not possible to say based on protein sequence conservation and modeling which are responsible for the different activities (Ceasar, Baker, Baker, Muench, Ignacimuthu, & Baldwin, 2016). Indeed, it has been reported that plant phosphate transporters may be able to switch between high‐ and low‐affinity modes (Ayadi et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…2). In a previous study, it was reported that all 12 foxtail millet PHT1s have the same conserved amino acids for Pi binding and H + and Pi transport as found in PiPT (Ceasar et al, 2016). The key resides involved in Pi binding for PiPT are tyrosine 150, glutamine 177, tryphtophan 320, aspartic acid 324, tyrosine 328, and asparagine 431 (Pedersen et al, 2013).…”
Section: Multiple Sequence Analysis Of Pht1 Proteins Of S Viridismentioning
confidence: 97%
“…Expression of SiPHT1;8 and SiPHT1;9 in roots was selectively induced by colonization with F. mosseae (Ceasar et al, 2014). Homology modeling was also performed for all these transporters, along with other characterized plant PHT1s (Ceasar et al, 2016), with the crystal structure of the Piriformospora indica phosphate transporter (PiPT) as a template (Pedersen et al, 2013). The phosphate‐binding site residues were found to be well conserved in SiPHT1 like in other plant PHT1 proteins such as Saccharomyces cerevisiae PHO84 phosphate transporter and PiPT.…”
Section: Nutrient Transporters Of Milletsmentioning
confidence: 99%
See 1 more Smart Citation